A new parameterization scheme for estimating surface energy fluxes with continuous surface temperature, air temperature, and surface net radiation measurements. Issue 2 (14th February 2014) - Lu, Jing; Tang, Ronglin; Tang, Huajun; Li, Zhao‐Liang
Abstract This study develops a method for estimating surface energy fluxes (surface sensible heat flux (H), latent heat flux (LE), and soil heat flux (G)) simultaneously from continuous observations of surface temperature (Ts), air temperature (Ta), and net radiation (Rn) without calculating various resistances. First, H, LE, and G are parameterized by some constant parameters that remain fairly invariant during a given day and some known functions related to Ts and Ta. Second, these constant parameters are solved by a minimization technique based on surface energy balance. Data from ground‐based measurements at the Yucheng station were used to evaluate the performance of the developed method. Results show that the simplified parameterization schemes well reproduce H, LE, and G with a root mean square error (RMSE) of ∼20 W/m2 at the instantaneous time scale, and perform better at the daily scale. For the estimates of H, LE, and G using the known Ts, Ta, and Rn measured at the Yucheng station as inputs, the RMSE is ∼60 W/m2 at the instantaneous time scale and ∼20 W/m2 at the daily scale. The requirement of continuous observations throughout a day in the developed method could be met by remotely sensed data from geostationary meteorological satellites. Fewer input variables and the obviation of calculating various resistances give the method the potential to generate surface fluxes over a large area.